Introducing underrepresented high school students to software engineering: Using the micro:bit microcontroller to program connected autonomous cars. Issue 3 (21st April 2020) - Kelly, Dylan G.; Seeling, Patrick
Abstract: Outreach that considers underrepresented groups has become one particular push to increase participation in Science, Technology, Engineering, and Math‐related disciplines, with Computer Science and Software Engineering representing one particular domain. We describe our outreach programming employing the micro:bit microcontroller environment for hands‐on software development and how students change their high‐level domain knowledge and attitudes. We find that overall, students were gaining general knowledge and slight increases in their positive attitudes towards a computer science‐related post‐secondary education. We also find differences between incoming knowledge level groups and self‐perception as well as performance differences. We also note a slight majority of students indicated that they liked our approach and that the utilization of the micro:bit microcontroller overall was worthwhile. Future iterations of our programming will utilize these findings and add additional data gathering efforts supplanting the current pre‐ and posttest instruments.